alien city. Grad u toku / alien city. The City In Progress: Marta Smolińska - Smolińska, Marta (AM Journal of Art and Media Studies, 2012)
This text is devoted to the phenomenon of the city that functions only in virtuality. And this is exactly the case with alien city — the virtual city “floating” in cyberspace at http://alien.mur.at/aliencity/index.php (created by alien productions from Vienna). Th e website address becomes the threshold of the city. alien city could be compared with the so-called ideal, perfectly laid out cities (for example Sforzinda by Filarete) and its dynamic structure could be juxtaposed with a monad, proposed by G.W. Leibnitz. It is processual, unstable, elusive and limitless. As a delocalized and nomadic structure alien city cannot have any stable history — in contrary, it’s history is changeable, indefi nite and, in fact, unpredictable.